2021
DOI: 10.53552/ijmfmap.2021.v07ii02.001
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal and theraptic properties of minor fruits - A Review

Abstract: A large number of minor and wild fruit species have originated in Indian subcontinent. Many of these fruits or their plants parts have been used in folk, Ayurvedic and Unani medicines since time immemorial. Several fruits were introduced in India during colonial period. Most of them adapted to climatic conditions of India but remains minor crops .These fruits also have several medicinal properties and were used by the native people of their respective origin of centres. Some the fruits such as bael, aonla, jam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Hepatoprotective, anti-inflammatory, and antioxidant effects of herbal medicines could be attributed to the presence of a variety of phytochemicals such as tannins, kaempferol, rutin, bergapten, psoralenes, flavonoids, coumarin, and phenolic glycosides ( 47 ). STZ-induced diabetic rats treated with S. torvum fruit extract showed decreased levels of ALT and AST indicating the hepatoprotective effect through maintenance of functional integrity of hepatic cell membrane and restoration of liver metabolism in diabetic rats ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatoprotective, anti-inflammatory, and antioxidant effects of herbal medicines could be attributed to the presence of a variety of phytochemicals such as tannins, kaempferol, rutin, bergapten, psoralenes, flavonoids, coumarin, and phenolic glycosides ( 47 ). STZ-induced diabetic rats treated with S. torvum fruit extract showed decreased levels of ALT and AST indicating the hepatoprotective effect through maintenance of functional integrity of hepatic cell membrane and restoration of liver metabolism in diabetic rats ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that STZ-induced diabetic rats showed a time-dependent rise in AST and ALT levels ( 52 ). Tripathi ( 47 ) reported hepatoprotective, anti-inflammatory, and antioxidant effects could be attributed to the presence of the various phytoconstituents including tannins, kaempferol, rutin, bergapten, psoralenes, flavonoids, coumarin, and phenolic glycosides. STZ-induced diabetic rats treated with S. torvum fruit extract showed decreased activity of ALT and AST enzymes that might support its hepatoprotective indicating maintenance of functional integrity of hepatic cell membrane, and normalization capability of impaired liver metabolism in diabetic rats ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to these compounds, it has strong antiviral, cardiotonic, and hyperglycaemic properties, which give it significant medical value. It is extensively utilized in both unani and ayurvedic therapy [ 7 ]. Aonla is used to manufacture ayurvedic medicines such as ashokarishta, chavanprash, triphalamasin, and triphala which are traditional specific formulations made by utilizing aonla fruit or with its powder [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sri Lanka is one of the biologically diverse hotspot in Asia, serving a home to more than 100 species of fruits. There are numerous underutilized wild fruit species that are used by the locals to suit their dietary needs (Tripathi, 2021). However, only a limited number of species are considered major fruits, including Banana, Mango, Pineapple, Passion Fruits and Avocado, which are cultivated on a commercial scale (Premathilake and Wathugala, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from their nutritional worth, some fruits offer therapeutic properties due to presence of flavonoids, quinolizidine, alkaloids, stilbenes, tannins, steroids, coumarin, and saponins, quinolizidine, triterpenoids, glycosides, and fatty acids. They are having a variety of pharmacological effects, including anti-inflammatory, analgesic, antidiabetic, antipyretic, antioxidant, hypoglycemic, hepatoprotective, and anticancer, dysentery, cholera, wounds, and sores (Tripathi, 2021). This review will present the nutritional and medicinal properties of selected minor crops in Sri Lanka, along with their potential for value-added products.…”
Section: Introductionmentioning
confidence: 99%